(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Despite national gains in antenatal care (ANC) coverage, women in urban slums remain vulnerable to gaps in service utilization and quality. Slum-specific evidence from Bhopal has been scarce. This study assessed ANC utilization, its pattern, associated factors, and reasons for non-use among women in Bhopal’s urban slums. Methods: A community-based cross-sectional study was conducted over three months. A total of 410 married women aged 20 years and above who had delivered their last child within the previous one year and residing in the selected slums were interviewed. A structured, pre-tested questionnaire captured socio-demographic details, ANC visits, timing, and place of care, iron-folic acid (IFA) intake, Tetanus and Diphtheria (TD) immunisation, and barriers. Data were analysed using SPSS 20.0, with chi-square tests for associations. Results: Almost all women (96.3%) had at least one ANC check‑up; 63.5% made four or more visits and 74.2% booked in the first trimester. Government facilities were the main source of care (60.3%). IFA consumption for the recommended 100 or more days was only 44.4%, with forgetfulness and side effects as leading reasons. TT coverage was substantially higher (85.6% with two doses or booster). Maternal education was the sole factor significantly associated with adequate ANC (71% among women with secondary or higher education vs. 51% among those with less education; p<0.001). Among the 15 women who did not attend any ANC, lack of transport (40%) and lack of knowledge or perception that care was unnecessary (26.7% each) were the primary barriers. Conclusion: While ANC contact coverage in Bhopal’s slums now approaches national averages, the quality and continuity of care—particularly IFA supplementation—remain deficient. Maternal education is the strongest predictor of adequate utilisation. Efforts must shift from achieving first contact to ensuring each visit is informative and supportive, with targeted outreach to overcome transport and awareness gaps among the least educated.